High-Fat Diet-Induced Obesity Modulates Colonic Lgr5 + Stem Cell Homeostasis by Dysregulating Plasma Membrane Organization. (29th May 2020) - Salinas, Michael; Fuentes, Natividad; Wang, Xiaoli; Fan, Yang-Yi; Callaway, Evelyn; Landrock, Kerstin; McMurray, David; Chapkin, Robert
Abstract: Objectives: The emerging obesity epidemic and its co-morbid conditions, such as colorectal cancer, pose a great challenge to global health and healthcare cost. This reinforces the urgent need to elucidate the underlying mechanisms contributing to the promotion of colon cancer in individuals with obesity. Extensive epidemiological studies have demonstrated a consistent and compelling association between obesity and the risk of cancer development and progression. Furthermore, our previous studies demonstrate that obesity induced by high-fat diet results in the expansion of the colonic stem cell pool during cancer initiation. However, the mechanistic link between obesity and the initiation and development of colon cancer remains elusive. Since the biophysical properties of the plasma membrane contribute to cellular signaling, we hypothesized that obesity alters colonic stem cell homeostasis via modulation of the biophysical properties of the plasma membrane, subsequently altering cell signaling events. Methods: Our studies utilized complementary in vivo and ex vivo mouse models including colonic organoids. Plasma membrane biophysical properties and cholesterol content were determined utilizing the physico-chemical sensitive dye, Di-4-ANEPPDHQ and Filipin III, respectively. Super-resolution stochastic optical reconstruction microscopy (STORM) was utilized to determine the nanoscale clustering of Wnt receptor, LRP6, and epidermal growth factor receptor (EGFR). Effects of nanoclustering on the activation status of downstream signaling targets was subsequently assessed. Results: High-fat diet induced obesity increased plasma membrane free cholesterol and rigidity of colonic crypts and Lgr5 + cells. The increase in rigidity was associated with an increase in the nanoclustering of key stem cell regulating membrane-bound receptors, LRP6 and EGFR. These biophysical perturbations were associated with changes in stem cell signaling and organoid-forming efficiency, a measure of stemness. Conclusions: Our results indicate that obesity alters the biophysical properties of the plasma membrane which influences the clustering and downstream signaling of membrane receptors. These findings are noteworthy because they may explain in part how obesity drives colon cancer progression. Funding Sources: This work was supported by NIH grant R35CA197707.